A Review of Pain Management Strategies in Postoperative Nursing Care - Johnson, Jasmi (AG Volumes, 2025)
The control of postoperative pain has a major impact on postoperative patient care. In order to minimize discomfort, encourage early mobilization, reduce complications, and improve overall recovery, effective pain management is crucial. Review the many studies on postoperative pain treatment techniques in this area. This review highlights the importance of multimodal analgesia (MMA) as a cornerstone of effective postoperative pain management in nursing care. By integrating pharmacologic options like opioids, NSAIDs, paracetamol, and adjuvants with regional techniques, MMA significantly reduces pain scores, opioid consumption, and associated side effects. Tailoring strategies to individual patient needs, surgical type, and cultural factors ensures optimal outcomes. MMA enhances patient comfort, shortens hospital stays, and promotes faster recovery, improving overall satisfaction. These findings underscore the need for flexible, patient-centered pain management protocols in nursing practice to achieve safer, more effective, and holistic postoperative care.